2017
DOI: 10.1105/tpc.17.00222
|View full text |Cite
|
Sign up to set email alerts
|

Homologs of PROTEIN TARGETING TO STARCH Control Starch Granule Initiation in Arabidopsis Leaves

Abstract: ORCID IDs: 0000-0003-3905-3647 (D.S.); 0000-0002-8569-9150 (J.B.); 0000-0001-8682-5668 (J.M.); 0000-0002-4440-1776 (T.B.S.); 0000-0002-9501-7854 (M.Z.); 0000-0002-2791-0915 (S.C.Z.)The molecular mechanism that initiates the synthesis of starch granules is poorly understood. Here, we discovered two plastidial proteins involved in granule initiation in Arabidopsis thaliana leaves. Both contain coiled coils and a family-48 carbohydrate binding module (CBM48) and are homologs of the PROTEIN TARGETING TO STARCH (PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
174
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 64 publications
15
174
1
Order By: Relevance
“…Like ss4 mutants, the ptst2 mutants have reduced numbers of starch granules, and this phenotype was exacerbated by loss of another homolog (PTST3; Seung et al, 2017). PTST2 was proposed to bind long malto-oligosaccharides with its carbohydrate-binding module and provide them as substrates to SS4 (Seung et al, 2017). This idea is broadly consistent with other observations that mutations affecting malto-oligosaccharide metabolism affect starch granule initiation (Malinova et al, 2017;Satoh et al, 2008;Seung et al, 2016).…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Like ss4 mutants, the ptst2 mutants have reduced numbers of starch granules, and this phenotype was exacerbated by loss of another homolog (PTST3; Seung et al, 2017). PTST2 was proposed to bind long malto-oligosaccharides with its carbohydrate-binding module and provide them as substrates to SS4 (Seung et al, 2017). This idea is broadly consistent with other observations that mutations affecting malto-oligosaccharide metabolism affect starch granule initiation (Malinova et al, 2017;Satoh et al, 2008;Seung et al, 2016).…”
supporting
confidence: 79%
“…2A). This is presumably because SS4C does not have selfpriming activity (Szydlowski et al, 2009) and rather relies on interaction with the recently described PTST2 and/or PTST3 proteins to deliver its substrates (Seung et al, 2017). Second, our YFP fluorescence data revealed that SS4C was uniformly distributed in chloroplasts, unlike the granule-surface localization of GS (Fig.…”
Section: The C-terminal Region Of Ss4 Alone Promotes Granule Initiatimentioning
confidence: 67%
See 3 more Smart Citations